Potensi Pesantren Sebagai Destinasi Wisata Halal Baru di Indonesia - Lailatul Qadariyah (Yos Soedarso Economic Journal (YEJ), 2019)
Pesantren is the oldest religious education institution in Indonesia. The education system and method applied are the strengths to produce experts in the field. In recent years the pesantren has not only focused on the study of religious knowledge but also other fields so it is not surprising that public interest continues to increase and not a few people are increasingly curious about the pesantren. This then becomes one of the reasons why pesantren should be considered as a tourist destination. Therefore the study of the potential of pesantren that can be "sold" as a tourist spot becomes quite important to be held. This research is a qualitative study which is to obtain data from interviews with caregivers, religious teachers and students and with observations. This study concludes that in order to become a tourist destination, pesantren has fulfilled 3 (three) things, namely Attraction, Facilities and Amenities as a basic requirement of developing tourist destinations. The results of this study will provide input for related parties to formulate the pesantren tourism model that is owned.Â Keywords: Potency; Boarding School; Halal Tourism